(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Fractures can occur at any age, but in modern times as the worldwide population grows older, the risk increases. Many of the fractures need metallic implants for a more efficient healing process and a reduced risk of complications. An implant can be used in orthopedic surgery if it can safely interact with the bone and the surrounding tissue. The most used materials in fracture management are metal alloys (Steel, Titanium, Cobalt-Chrome) that need to be compatible with tissue, however, they do not stimulate the healing process. Physiotherapy could improve the bone/implant interaction by stimulating the local metabolism and cell proliferation while also reducing local symptoms such as pain. The advantages of using LASER therapy are: a reduced number of contraindications, the availability of the equipment in rehabilitation facilities, and the compliance of patients as there is no discomfort during the procedure. The main drawback of using LASERs in bone stimulation is that there is no consensus in protocol usage between researchers because of the multitude of parameters. Through this article, we aim to shed some light on the use of LASER therapy in implant osseointegration and bone healing. Keywords: implant osseointegration, implant stability, Low-level LASER therapy, Photobiomodulation, Physiotherapy, bone